PENERAPAN LEARNING MANAGEMENT SYSTEM (LMS) PADA SEKOLAH MENENGAH PERTAMA DAN SEKOLAH MENENGAH ATAS - Panji Wisnu Wirawan; Moch. Abdul Mukid (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Learning Management System (LMS) is a software package  which providesvirtual classes for both teacher and student. LMS can be deployed to localschool networks and can be installed on the school's website. Hence it is easierfor students and teachers in Junior and Senior High School to access learningmaterials. Junior High School and Senior High Schools have many classes andeach class has many subjects in each academic year. To apply the learningsupported by the LMS, a good understanding of LMS features is required, sothat LMS can be used to support many of the classes and subjects. This studyproposes an LMS implementation scheme in Junior High School and SeniorHigh School so that LMS can support many classes and subjects. Specifically,Moodle was selected as LMS product in this study. Firstly, we identify howclass was organized in both junior and senior high school. We continued withidentification moodle features that could support multi class organization. Theresult of this study was a scheme of how Moodle can be implemented to supportmulti class organization in junior and senior high school. Keywords: Learning Management System (LMS), Moodle, multi class organization